ANALISIS POTENSI PENGEMBANGAN OBYEK WISATA PULAU PUTRI DIDAERAH NONGSA, BATAM, KEPULAUAN RIAU - Anatasya, Rheva; Rahmadani, Yuniar; Nur Tasya; Rafi Septiadi; Najwa Rachel (Puslitabmas Batam Tourism Polytecnic, 2025)
The Batam City government area is home to various beautiful islands and amazing underwater worlds, including the island opposite Nongsa or known as Putri Island. One of Indonesia's outermost islands, Putri Nongsa Island, which is the direct border between Indonesia and neighboring countries, is located on the edge of the Malacca Strait, across the busiest Phillips Strait in the world, and directly borders Singapore and Malaysia. When the team explored Putri Island, we saw huge tourism potential if it could be managed well.